THE SHARING ECONOMY AND THE DEVELOPMENT OF INDEPENDENT TOURISM IN THE DIGITAL ERA - Yuldashev Kamol Sharifovich, (TADQIQOTLAR, 2026)
Abstract.  The  development  of  the  sharing  economy  became  one  of  the  most significant trends in the transformation of contemporary tourism. The spread of online platforms  based  on  the  principles  of  collaborative  consumption  gave  independent travelers the opportunity to organize transport, accommodation, and the exchange of experience  directly  with  other  participants,  without  the  mediation  of  traditional agencies. The present article examines the formation of peer-to-peer tourism services, from online vehicle rental to hospitality exchange and ride sharing communities, and it analyzes the model of interaction between resource providers, digital platforms, and travelers. Particular attention is given to the role of trust, of user reviews, and of the proportional division of costs, as well as to the contribution of the sharing economy to the autonomy of travelers and to the ecological sustainability of tourism.